(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
A 22 years young lady, normotensive, non-diabetic patient persented clinically with right sided weakness, headache, visual blurring & repeated convulsion. She had history of vaginal delivery 2 weeks ago . Examination revealed patient to be mildly anaemic and moderately dehydrated. She was confused & disoriented,speech was slurred & incoherent. Pupil was moderately dilated bilaterally and reaction was sluggish , mild degree opthalmoparesis especially in abduction. On Fundoscopy , bilateral Papillloedima was persent. Muscle Power was reduced in right side of body, proximally grade 3 distally grade2, right sided plantar was extensor. Investigation revealed neutrophilic leukocytosis, ESR-45 mm in 1sthour,all others metabolic profile was normal. ANA and anticardiolipin antibody was negative but D-dimer was positive.CT scan of brain showed multiple small hemorrhagic spot in parietal and temporal region and MRI of brain with contrast showed bifrontal venous infarct with hemorrhagic transformation with evidence of thrombosis of posterior aspect of superior sagittal sinus.Treatment was given with inj. Dexamethasone, Anticonvulsant, ,Enoxaperin and Acetazolamide. Patient vapidly improved and aspirin was added and discharged with advice. On subsequent pregnancy patient did not develop such complication after delivery J.Dhaka National Med. Coll. Hos. 2013; 19 (02): 55-57